Adrenal relapse of primary central nervous system diffuse large B-cell lymphoma: A case report. Issue 38 (September 2018) - Ma, Shuang; Sen, Siddhartha Sen; Jug, Rachel; Zhang, Xuefeng; Zhang, Wan-Lin; Shen, Shuai; Yu, Cheng-Qian; Xu, Hong-Tao; Yang, Lian-He; Wang, Endi
Abstract: Rationale: Primary central nervous system lymphoma (PCNSL) is a rare form of non-Hodgkin lymphoma with a dismal outcome. Most patients relapse in intracranial sites and <5% of patients relapse in extracranial sites. Here, we present the first case of PCNSL with an adrenal relapse. Patient concerns: A 72-year-old woman, first presented 7 years ago with complaints of headache and dizziness. Diagnoses: Enhanced magnetic resonance imaging revealed the mass within the splenium of the corpus callosum. On histological examination, there was a diffuse growth pattern of neoplastic cells in the brain biopsy. Immunohistochemistry and flow cytometric analysis demonstrated that the neoplastic cells were of B-cell lineage. Interventions: The patient underwent methotrexate-based chemotherapy and whole-brain radiotherapy after the initial diagnosis of primary central nervous system-large B-cell lymphoma (CNS-DLBCL). Outcomes: After 4 years of clinical remission, the patient was diagnosed with endometrial cancer. Interestingly, a radiological study following the treatment of endometrial cancer demonstrated a right adrenal mass, which was suspicious for malignancy. Morphologic examination and immunohistochemistry studies confirmed the diagnosis of diffuse large B-cell lymphoma. A fluorescent in situ hybridization panel for lymphoma showed rearrangement of Immunoglobulin heavy chain (IGH) and B-cell lymphoma 6 (BCL6), respectively, suggesting fusion of BCL6/IGH. Immunoglobulin kappa analysis demonstrated a common origin for the brain and adrenal lesions, which led to the final diagnosis of an adrenal relapse of CNS-DLBCL. Lessons: PCNSL is a highly infiltrative neoplasm, particularly at relapse. To the best of our knowledge, this is the first case of CNS-DLBCL with adrenal relapse. Considering the poor outcome of CNS-DLBCL, molecular genetic studies should be done to identify a common origin for the primary and secondary lesion.